2014
DOI: 10.5455/2320-6012.ijrms20141113
|View full text |Cite
|
Sign up to set email alerts
|

Role of alcoholism in liver abscess

Abstract: Background: This retrospective study was conducted on 108 patients to find the role of alcoholism in liver abscess. Methods: The present study was undertaken on patients both male and female admitted in surgical wards of Chennai medical college & hospital. 108 patients were taken up for the study from the surgical wards of the hospital over a period of 1½ year i.e., from January 2013 to June 2014. Results: The disease usually affects the males in the age group 25-55 years, alcoholism is found to be the chief p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Unlike alcoholism and malnutrition (hypoalbuminemia), low socioeconomic status was not independently associated with complications of ALA. The following mechanisms have been proposed for the predisposition of ALA by alcohol: (i) alcohol suppresses the function of Kupffer cells, which has the important role of clearing the amoeba; (ii) hepatocyte damage by alcohol; (iii) hepatic accumulation of iron; (iv) the invasive capacity of EH is facilitated by alcohol; (v) nutritional deficiencies in alcoholics leading to lowered body resistance and suppression of liver function; (vi) alcohol depress activity of immunity; and (vii) entry of EH into the blood facilitated by dysbiosis of intestinal bacteria and alcohol‐induced intestinal hyperpermeability …”
Section: Discussionmentioning
confidence: 99%
“…Unlike alcoholism and malnutrition (hypoalbuminemia), low socioeconomic status was not independently associated with complications of ALA. The following mechanisms have been proposed for the predisposition of ALA by alcohol: (i) alcohol suppresses the function of Kupffer cells, which has the important role of clearing the amoeba; (ii) hepatocyte damage by alcohol; (iii) hepatic accumulation of iron; (iv) the invasive capacity of EH is facilitated by alcohol; (v) nutritional deficiencies in alcoholics leading to lowered body resistance and suppression of liver function; (vi) alcohol depress activity of immunity; and (vii) entry of EH into the blood facilitated by dysbiosis of intestinal bacteria and alcohol‐induced intestinal hyperpermeability …”
Section: Discussionmentioning
confidence: 99%
“…Further, Raja and Karthick [ 16 ] suggested that the invasive capacity of E. histolytica is facilitated by alcohol which is harmful to the liver and by nutritional deficiencies in alcoholics, thus leading to a higher incidence of ALA in alcoholics. Further, they reported that duration and quality of alcohol consumed also play an important role in the higher incidence of liver abscess and therefore alcoholism is the most important predisposing factor [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Raja and Karthick [ 16 ] further reported that though alcoholism seems to be the predisposing factor, it has no role in the aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the deficiency in vital body elements leads to malnutrition, which results in the susceptibility of the body against various diseases [ 92 ]. Raja and Karthick [ 93 ] demonstrated that due to nutritional deficiency, alcoholics are more susceptible to Entamoeba histolytica infection. However, since iron is a vital element for Entamoeba histolytica , iron deficiency in women who have regular menstrual blood loss could prevent the risk of Entamoeba histolytica infection [ 94 ].…”
Section: Discussionmentioning
confidence: 99%